The application of patent analysis to assess the prospects of import substitution (on the example of domestic anorexicly and crosslinking products) - T. N. Erevantseva (Ekonomika Nauki)
In the framework of the implementation of the import substitution policy of the Ministry of industry and trade issued order No. 655 dated March 31, 2015 “On approval of the action plan on import substitution in branches of the medical industry of the Russian Federation” according to which the share of imports in the majority of medical devices in 2015 amounted to 80–100%, but by 2020 should be reduced up to 10–20%. Analyzed inventive activity of domestic and foreign inventors in the field of anorexically and crosslinking products, which is celebrated in Russia.The data obtained do not allow to characterize scientific and technological backlog of the Russian Federation in the field anorexicly and crosslinking products as competitive. The possibility of achievement of indicator Order No. 655 of the Ministry of industry and trade of import substitution at the level of 40–50% by 2020, assessed as extremely low. The analysis of patent documents do not allows us to hope that Russian manufacturing companies are ready to offer mass production for the domestic market and capture niche global market. The рatent activity of foreign companies indicates that they are at the present time and next during the term of their patent monopoly for the production and sale in the domestic market these products.